Variasi Regim Lengas dan Suhu Tanah Pada Lahan yang Mengalami Penutupan Awan Rendah Berbasis Peta Terra Modis di Pulau Lombok - Reni Anggraeni; Mahrup Mahrup; IGM Kusnarta; Putu Silawibawa (Department of Soil Science, Faculty of Agriculture, University of Mataram, 2022)
Soil moisture and temperature are parameters of soil physical properties that are closely related to climatic variations. Descriptive Research on